Peramalan Indeks Harga Perdagangan Internasional Berdasarkan Data Bulan Januari 2021 – Mei 2022 Menggunakan Metode Double Brown Exponential Smoothing - Edwardo Muraema; Lisnur Wachidah (Bandung Conference Series: Statistics, 2023)
Abstract. The International Trade Price Index [IHPI] measures changes in the components of the aggregate price of trade in goods and services between residents of an economy and the rest of the world. The index that measures the average change in commodity prices over time at the wholesale level is known as the International Trade Price Index [IHPI]. Based on data obtained from BPS publications in the form of International Trade Price Index [IHPI] data for January 2021 - May 2022. Based on these data the author will forecast for the next 7 months for June - December 2022 using the Double Brown Exponential Smoothing method, based on the research results obtained International Trade Price Index [IHPI] with the smallest or best Mean Square Error results at α = 0.6 of 0.089. Based on the results of forecasting for the next 7 months, for the International Trade Price Index [IHPI] the forecast results for the 18th period are obtained, namely for June 2022 of 111.061. The forecast result for the 19th period for July 2022 is 111.683. The forecast result for the 20th period for August 2022 is 112.305. The forecast result for the 21st period for September 2022 is 112.927. The forecast result for the 22nd period for October is 113.549. The forecast result for the 23rd period for November is 114.171. The forecast result for the 24th period for December 2022 is 114,793. The forecasting results are expected to assist the government in predicting the International Trade Price Index [IHPI] earlier so that the government is able to anticipate and control the prices of goods and services. Abstrak. Indeks Harga Perdagangan Internasional [IHPI] mengukur perubahan komponen harga agregat perdagangan barang dan jasa antara penduduk suatu perekonomian dan seluruh dunia. Indeks yang mengukur rata-rata perubahan harga komoditas dari waktu ke waktu di tingkat grosir yang dikenal sebagai Indeks Harga Perdagangan Internasional [IHPI]. Berdasarkan data yang diperoleh dari hasil publikasi BPS berupa data Indeks Harga Perdagangan Internasional [IHPI] pada bulan Januari 2021 – Mei 2022. Berdasarkan data tersebut penulis akan melakukan peramalan selama 7 bulan ke depan untuk bulan Juni – Desember 2022 dengan menggunakan metode Double Brown Exponential Smoothing, berdasarkan hasil penelitian didapatkan Indeks Harga Perdagangan Internasional [IHPI] dengan hasil Mean Square Error terkecil atau yang terbaik pada α = 0,6 sebesar 0,089. Berdasarkan hasil dari peramalan selama 7 bulan ke depan, untuk Indeks Harga Perdagangan Internasional [IHPI] diperoleh hasil ramalan untuk periode ke-18 yaitu untuk bulan Juni 2022 sebesar 111,061. Hasil ramalan untuk periode ke-19 untuk bulan Juli 2022 sebesar 111,683. Hasil ramalan untuk periode ke-20 untuk bulan Agustus 2022 sebesar 112,305. Hasil ramalan untuk periode ke-21 untuk bulan September 2022 sebesar 112,927. Hasil ramalan untuk periode ke-22 untuk bulan Oktober sebesar 113,549. Hasil ramalan untuk periode ke-23 untuk bulan November sebesar 114,171. Hasil ramalan untuk periode ke-24 untuk bulan Desember 2022 sebesar 114,793. Hasil peramalan tersebut diharapkan dapat membantu pemerintah dalam memprediksi Indeks Harga Perdagangan Internasional [IHPI] lebih awal agar pemerintah mampu mengantisipasi sekaligus mengontrol harga barang dan jasa.